Pola Komunikasi pada Anak yang Kecanduan Handphone di Dalam Keluarga: - Nur Sabdia; Zuhriah Zuhriah (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Communication is one of the most appropriate elements to shape the character of children in the family, but along with the rapid pace of communication technology begins to erode and fascive because children's lives are closer to the technology. This research is a type of qualitative research that aims to describe how communication patterns in children who are addicted to cellphones in the family. The results of this study show that the communication pattern that occurs in children who are addicted to mobile phones in Bandar Kumbul village, West Bilah District, Labuhan Batu Regency is a permissive communication pattern or provides freedom for children to play mobile phones, this is based on the results of observations and interviews that researchers conducted on 10 informants studied, the results were 6 families who applied this communication pattern, Communication is not built effectively because parents do not provide restrictions for children to play mobile phones as a result the opportunity for children to establish communication with family at home is very less because he comes home from school immediately plays online games with his friends, this factor also indicates that the cause of children's addiction to mobile phones due to the communication patterns that the family creates seems to liberate children, So that children feel comfortable and happy with their android. Keywords: Communication Patterns, Mobile Phone Addiction, Children and Family